Differences in head size and shape during the growth of Deutero Malay children - Primasari, Ameta; Angelia, Veronica; Agara, Dimas (Padjadjaran Journal of Dentistry, 2019)
Introduction: The growth periods of 0-18 years old can be studied with anthropometry by identifying the head size and shape of the human head. Study on vertical, transverse, and horizontal cephalic indexes can understand differences and growth between sexes and age groups. This study was aimed to analyse the averages and differences in the head size and shape of Deutero Malay children in different age groups. Methods: This research was a descriptive analytic study with cross-sectional design. The sample of 192 Deutero Malay children consisted of boys and girls with an age range of 7-18 years old. Measurement of head height, length, and width was performed to calculate the differences of vertical, transverse, and horizontal cephalic index values by sex and age group, and the classification of the head shape based on the cephalic index values. Results: There was a difference of vertical, transverse, and horizontal by age group, with p = 0.000 (p < 0.05). The average of vertical, transverse, and horizontal cephalic index values was significantly higher in each age group. The average horizontal cephalic index was significantly higher in boys and girls. There was no significant difference in the head shape by the vertical and horizontal cephalic index in all age groups. The highest vertical cephalic index found was chamaecephalic (68%). The highest transverse cephalic index was tapeiocephalic (99%). The highest horizontal cephalic index was hyperbrachycephalic (80%). Conclusion: There is similar head shape of Deutero Malay children, although there may be increasing head size along with age. Keywords: Deutero Malay, head shape, cephalic index, transverse cephalic index, horizontal cephalic index, vertical cephalic index